Religious Violence Through Lens of Cavanaugh’s Theory: The Case of Burning Vihara in Tanjungbalai - Mufdil Tuhri (Intizar, 2020)
The incident of burning houses of Buddhist worship and destruction of ethnic Chinese dwellings in Tanjungbalai occurred on 29-30 July 2016. Local communities, regional leaders, security forces and some religious leaders considered this incident to be motivated by religious issues and ignored several other factors such as ethnicity, social political economy and so on, while many observers-academic, researchers, policy-makers, journalists, NGO workers, political commentatirs, among others- argues that religious violence analysis really motivated by material-based political interests, socio-economic reason, and others factor of secular ones and dismissed the religious framing of the violence. This research is based on Cavanaugh's theory that there is no purely religious or other ideological factor that is seen as dominant for the occurrence of violence. This article argues that religion plays a role in conflict dynamics in Tanjungbalai as an instrumental reason, but at the same time, attacks on Buddhist temples in Tanjungbalai are complex issues that do not purport to reveal the true state of affairs. What is apparent in riot in Tanjungbalai is competition from religion and secular factor including competition over public space, socioeconomic status, religious zoning are suggested as reasons why violent tension may exist in Tanjungbalai.